(untitled) (Bangladesh Journal of Nuclear Medicine, 2024)
Purpose: The primary objectives of this study were threefold: first, to comprehensively assess radiation exposure levels within the Nuclear Medicine (NM) institution; second, to identify and address potential risks associated with diagnostic and therapeutic procedures; and third, to establish strong control measures and emergency response plans. These goals collectively aim to contribute to the creation of a personalized radiation protection program that addresses the unique issues provided by NM applications. Materials and Methods: Radiation doses were computed over a six-month period using survey meter data gathered three times each day. Measurements were carried out in ionization chambers using radiation’s ionizing properties. Continuous radiation surveys used digital survey meters in designated regions, which were classified according to dose rates, with a focus on monitoring doses from radiopharmaceuticals such as 131I and 99mTc. Results: Continuous radiation surveys over six months identified maximum values in specific areas within the institution, such as the SPECT room and therapy patient room, all below the allowable limit. This ensured the safety of personnel and patients while maintaining ambient radiation levels outside the institution consistently below the permissible limit. Conclusion: This study provided essential data for establishing a dose reduction strategy in a clinical NM facility, confirming INMAS Bogura as free from radiation-induced risks and emphasizing the importance of continuous evaluation, adherence to regulations, and long-term monitoring to ensure safe radiological working conditions. Bangladesh J. Nuclear Med. 27(1): 39-43, 2024